Detection of macrophages via paramagnetic vesicles incorporating oxidatively tailored cholesterol ester: an approach for atherosclerosis imaging - Maiseyeu, Andrei (2010)
AIM: Macrophages play a key role in the initiation, progression and complications of atherosclerosis. In this article we describe the synthesis of biocompatible, paramagnetic, fluorescent phosphatidylserine vesicles containing cholesterol ester with a free carboxylic acid function and its use for targeted imaging of macrophages. METHODS & RESULTS: We synthesized anionic vesicles containing a combination of phosphatidylserine and a novel synthetic oxidized cholesterol ester derivative (cholesterol-9-carboxynonanoate [9-CCN]). In vitro studies to characterize particle size, MRI relaxation times and stability were performed. Vesicles containing 9-CCN demonstrated enhanced ability to bind human low-density lipoprotein and to be internalized by macrophages. Experiments in cultured macrophages with 9-CCN vesicles, alone and in the presence of low-density lipoprotein, indicated uptake of vesicles through scavenger receptor and integrin-dependent pathways. In vivo MRI using 9-CCN vesicles containing gadolinium in a rabbit model of atherosclerosis revealed protracted enhancement of 9-CCN vesicles and colocalization with arterial macrophages not seen with control vesicles. Pharmacokinetic experiments demonstrated prolonged plasma residence time of 9-CCN vesicles, perhaps due to its capacity to bind to low-density lipoprotein. CONCLUSION: Vesicles containing 9-CCN demonstrate prolonged plasma and plaque retention in experimental atherosclerosis. Such a strategy may represent a simple yet clinically relevant approach for macrophage imaging.